The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/jacs.7b11010
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Methane on Single-Atom Catalyst of Rhodium Dispersed on Zirconia for Direct Conversion

Abstract: Direct methane conversion into value-added products has become increasingly important. Because of inertness of methane, cleaving the first C-H bond has been very difficult, requiring high reaction temperature on the heterogeneous catalysts. Once the first C-H bond becomes activated, the remaining C-H bonds are successively dissociated on the metal surface, hindering the direct methane conversion into chemicals. Here, a single-atom Rh catalyst dispersed on ZrO surface has been synthesized and used for selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
295
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(312 citation statements)
references
References 48 publications
(63 reference statements)
15
295
1
1
Order By: Relevance
“…[7][8][9][10] Fortunately, a mass of recent studies have demonstrated that Fe-N x -based carbon nanomaterials represent one of the most promising alternatives to PGM-based catalysts for ORR because of their extraordinary catalytic performance, together with a relatively cheap price and abundant reserves. [13][14][15][16] Due to the low coordination, maximum atom utilization efficiency, and most exposed active sites, isolated single atom (ISA) catalysts usually exhibit exceptional catalytic performances and thereby have triggered considerable interests. [13][14][15][16] Due to the low coordination, maximum atom utilization efficiency, and most exposed active sites, isolated single atom (ISA) catalysts usually exhibit exceptional catalytic performances and thereby have triggered considerable interests.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Fortunately, a mass of recent studies have demonstrated that Fe-N x -based carbon nanomaterials represent one of the most promising alternatives to PGM-based catalysts for ORR because of their extraordinary catalytic performance, together with a relatively cheap price and abundant reserves. [13][14][15][16] Due to the low coordination, maximum atom utilization efficiency, and most exposed active sites, isolated single atom (ISA) catalysts usually exhibit exceptional catalytic performances and thereby have triggered considerable interests. [13][14][15][16] Due to the low coordination, maximum atom utilization efficiency, and most exposed active sites, isolated single atom (ISA) catalysts usually exhibit exceptional catalytic performances and thereby have triggered considerable interests.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, methanol was the exclusive product on Rh 1 /TiO 2 single atom catalysts, which lacked the acidity of H-ZSM-5. Another synchronous work also found that the reaction of methane to methanol was facile on Rh 1 /ZrO 2 [11]. Thus through modulating the acidity of the support, the desired product of acetic acid or methanol can be tuned.…”
Section: Rh Single Atom Catalyst For Direct Conversion Of Methane To mentioning
confidence: 94%
“…Further investigations suggest that a two‐step reaction pathway is responsible for the conversion of methane to oxygenates, in which methane is first activated to produce Rh‐CH 3 , followed by oxygen insertion to produce methanol or CO insertion to produce acetic acid. In another study, Lee and co‐workers introduced a single‐atom Rh catalyst using ZrO 2 as support materials for selective activation of methane . The reaction was performed using H 2 O 2 in the aqueous solution or using O 2 in gas phase as oxidant, producing methanol and ethane, respectively.…”
Section: Catalytic Heterogeneous Reactionsmentioning
confidence: 99%
“…In another study, Lee and co-workers introduced a single-atom Rh catalyst using ZrO 2 as support materials for selective activation of methane. [119] The reaction was performed using H 2 O 2 in the aqueous solution or using O 2 in gas phase as oxidant, producing methanol and ethane, respectively. In addition to acetic acid and methanol, the direct conversion of methane to methyl acetate is also attractive.…”
Section: Methane Conversionmentioning
confidence: 99%